Political orientation and mental health during a socio-political crisis in Israel: the intermediary role of the hostile-world scenario - Avidor, Sharon; Shmotkin, Dov (Frontiers in Social Psychology, 2025)
IntroductionThere are still unanswered questions regarding psychological underpinnings of political orientations, especially in time of political rifts. This study examined differences in mental health (wellness and distress) and attitudinal concomitants (behavioral intentions and concerns over core social issues) between leftists and rightists in Israel, during a socio-political crisis over the right-wing government's attempt, in 2023, to conduct a judicial overhaul. The theoretical model of the hostile-world scenario (HWS), referring to an image of major threats in life, was applied as a psychological construct that might link political orientation with mental health.MethodA convenience sample was administered online questionnaires. Following a case-control matching, groups originally included self-declared 264 leftists, 258 centrists, and 264 rightists (mean age = 54, SD = 16).ResultsDiscriminant analysis found leftists strongly separated from rightists on both intentions and concerns. Centrists also came up as a separate group, but with weaker discriminant functions, and thus were not included in subsequent analyses. Leftists and rightists did not differ in wellness (life satisfaction, positive affect, purpose in life, personal growth), yet leftists had higher distress (negative affect, anxiety, depressive symptoms). Notably, the HWS positive engagement mode (rather than the parallel HWS negative engagement) was a consistent mediator between political orientation and all the mental health indicators, suggesting that links between political orientation and mental health were largely explained by a self-reassuring approach toward harsh representations of the hostile world. Such an approach appeared stronger among rightists. Analyses were conducted with, as well as without, controlling for religiousness and education, as they emerged as major concomitants of political orientation.DiscussionCurrent findings may shed light on coping styles that are differentially preferred by leftists and rightists, with consequences emerging not just in social spheres, but also in terms of mental health on the individual level.